2000
DOI: 10.2460/javma.2000.216.1571
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic assessment of antianxiety medication in dogs and correlation with serum drug concentration

Abstract: Amitriptyline and clomipramine administered at standard dosages apparently do not cause ECG abnormalities in healthy dogs with behavioral problems. These medications should be used cautiously in dogs with conduction abnormalities, and clinicians should periodically monitor ECG and use good clinical judgment to weigh risks and benefits of medications for the safety of each dog.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 13 publications
0
12
0
1
Order By: Relevance
“…Amitriptyline should be used cautiously in dogs with conduction abnormalities as it may cause ECG changes and, at higher doses, ventricular arrhythmias (Reich et al . ). It should not be used with tramadol, St. John's wort and other drugs that act via serotonin and norepinephrine reuptake, as they may have interactions that lead to serotonin syndrome (Ener et al .…”
Section: Therapies In Chronic Painmentioning
confidence: 97%
See 1 more Smart Citation
“…Amitriptyline should be used cautiously in dogs with conduction abnormalities as it may cause ECG changes and, at higher doses, ventricular arrhythmias (Reich et al . ). It should not be used with tramadol, St. John's wort and other drugs that act via serotonin and norepinephrine reuptake, as they may have interactions that lead to serotonin syndrome (Ener et al .…”
Section: Therapies In Chronic Painmentioning
confidence: 97%
“…There are no controlled trials of their use in dogs but amitriptyline has been reported to be beneficial in a case series of three dogs with neuropathic pain (Cashmore et al 2009). Amitriptyline should be used cautiously in dogs with conduction abnormalities as it may cause ECG changes and, at higher doses, ventricular arrhythmias (Reich et al 2000). It should not be used with tramadol, St. John's wort and other drugs that act via serotonin and norepinephrine reuptake, as they may have interactions that lead to serotonin syndrome (Ener et al 2003).…”
Section: Tricyclic Antidepressantsmentioning
confidence: 99%
“…Συνήθως, επιλέγεται η χλωμιπραμίνη, επειδή παρουσιάζει τις μικρότερες παρενέργειες, σε αρχική δόση 1 mg/kg σ.β. per os, κάθε 12 ώρες, η οποία μπορεί να διπλασιαστεί ή τριπλασιαστεί, εφόσον δεν υπάρχει ικανοποιητικό αποτέλεσμα εντός 2 έως 4 εβδο μάδων (Hewson et al 1998, MacDonald and Bradley 2000, Reich et al 2000, Landsberg 2001, Seksel and Lindeman 2001, Virga 2003, Crowell-Davis 2006, Tapp and Virga 2012. Οι εκλεκτικοί αναστολείς επαναπρόσληψης της σεροτονίνης, που έχουν επίσης Πίνακας 4.…”
Section: θεραπευτικη αντιμετωπισηunclassified
“…Conversely, the owner reported a worsening of aggression during walks. Clomipramine was selected because it has been approved for use in dogs, has been used to treat aggression in many species, [21][22][23] and has mild sedative effects 18 that were desirable for keeping the dog calm during counter-conditioning exercises during walks. The dog' s arousal level during walks appeared to be hindering the owner' s counterconditioning attempts, despite an appropriate dosage of paroxetine.…”
Section: Treatmentmentioning
confidence: 99%